2021
DOI: 10.3390/gels7040186
|View full text |Cite
|
Sign up to set email alerts
|

Glyceraldehyde as an Efficient Chemical Crosslinker Agent for the Formation of Chitosan Hydrogels

Abstract: The rheological changes that occur during the chemical gelation of semidilute solutions of chitosan in the presence of the low-toxicity agent glyceraldehyde (GCA) are presented and discussed in detail. The entanglement concentration for chitosan solutions was found to be approximately 0.2 wt.% and the rheological experiments were carried out on 1 wt.% chitosan solutions with various amounts of GCA at different temperatures (25 °C and 40 °C) and pH values (4.8 and 5.8). High crosslinker concentration, as well a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 77 publications
0
3
0
Order By: Relevance
“…This effect likely occurred because increasing the polymer concentration increased the polymer network packing density, which slowed coating degradation and impeded the release of incorporated pDNA molecules. 56,57 We also found that GTA crosslinking decreased pDNA release for the collagen and acidic gelatin-coated PCL scaffolds, while the GTA-crosslinked basic gelatin-coated PCL scaffolds suspended pDNA release (Figure 4E). We further confirmed the significant influence of GTA concentration on the release of pDNA, particularly in basic gelatin, as opposed to acidic gelatin.…”
Section: Natural Polymer Coating and Crosslinking Concentrations Infl...mentioning
confidence: 65%
“…This effect likely occurred because increasing the polymer concentration increased the polymer network packing density, which slowed coating degradation and impeded the release of incorporated pDNA molecules. 56,57 We also found that GTA crosslinking decreased pDNA release for the collagen and acidic gelatin-coated PCL scaffolds, while the GTA-crosslinked basic gelatin-coated PCL scaffolds suspended pDNA release (Figure 4E). We further confirmed the significant influence of GTA concentration on the release of pDNA, particularly in basic gelatin, as opposed to acidic gelatin.…”
Section: Natural Polymer Coating and Crosslinking Concentrations Infl...mentioning
confidence: 65%
“…In the literature, there are some experimental papers ,, on salt-free polyelectrolyte solutions that are consistent with the theoretical prediction of α = 0.5 and β = 1.5. However, there are also other studies ,,, in the literature on salt-free polyelectrolyte solutions where β = 1.5 was never observed, but values of β in the range of 3–4 were reported.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, the gelation time needed to be identified to ensure the formation of a three-dimensional network. Several techniques, such as light scattering (LS) [12,33], beam diffraction [13], and rheology [34][35][36], have been widely used to elucidate the mechanism of material gelation and its molecular structure. In this work, the rheological technique was used to investigate the crosslinking behavior due to its direct correlation with the evolving physical and mechanical properties of the system during the crosslinking process.…”
Section: Uv-induced Sol-to-gel Transition Of Pnipam Solutionmentioning
confidence: 99%